The role of InGaN quantum barriers in improving the performance of GaN-based laser diodes. (January 2022) - Ben, Yuhao; Liang, Feng; Zhao, Degang; Yang, Jing; Liu, Zongshun; Chen, Ping
Highlights: InGaN quantum barrier (QB) layers can effectively improve the optical field distribution and increase the optical confinement factor. The homogeneity of MQWs is improved greatly when using InGaN QB layers. The slope efficiency of LD using InGaN quantum barrier layers is 34.3% higher than that of LD using GaN quantum barrier layers. However, the InGaN QB layers will lead to bigger leakage current. Abstract: In this work, different aspects which have influences on device performance of blue laser diodes (LDs) when using InGaN instead of GaN as quantum barrier (QB) layers are investigated theoretically and experimentally. In the modeling calculation, it is found that the threshold current of LDs with InGaN QB layers is reduced obviously, but the slope efficiency is not largely improved due to the increase of leakage current. However, in the experimental results of the fabricated LDs using InGaN QB layers in comparison with those with GaN QB layers, the slope efficiency is really improved greatly, which is 34% higher. The great improvement of emission efficiency is ascribed to the better homogeneity of the active region which can improve the peak mode gain effectively. Such a better homogeneity of QW layers can be mainly attributed to the decreased composition pulling effect and a suppression of the stress between InGaN QB layers and InGaN QW layers.